PERMIAN-TRIASSIC BOUNDARY OF INDIAN SUBCONTINENT AND ITS INTERCONTINENTAL CORRELATION (Journal of Sciences, Islamic Republic of Iran)
The Permian-Triassic boundary in the Himalayas is reviewed and discussed in the light of palaeontologic and stratigraphic data collected during the past two and a half decades from Kashmir, Spiti and Nepal. The deposition of the Kuling Shales and their equivalents in different parts of the Himalayas was followed by shallowing and regression of the sea. Sedimentation was interrupted at the top of Kuling Shale sequence resulting in the emergence of many areas. This was followed by widespread and simultaneous marine transgression resulting in deposition of Otoceras-bearing beds. Otoceras woodwardi Zone has been assigned to the Griesbachian age. The base of Ophiceras tibeticum Zone corresponds to the base of Isarcicella isarcica conodont zone; the disappearance of Otoceras, Permian brachiopods and other holdovers. It is suggested that the base of Gyronites frequens Zone is the most befitting for demarcating and documentation of the Perrnian- Triassic boundary as this stratigraphic level corresponds to the end of the lowest faunal diversification and coincides with the Griesbachian-Dienerian boundary. This boundary is also marked by striking changes in conodont fauna from Anchignathodus and Zsarcicella to Kashmirella and Neospathodus